Empowerment of Enrekang Coffee Farmers: Innovation of Coffee Skin Waste Into an Alternative Fermentation Feed Through Counseling Approach - Sudirman, M Yunus; Kining, Ekajayanti; Ardat, Muh Achyar; Suharman, Suharman; Rusdin, Rista Astari; Astin, Nur (Asosiasi Ide Bahasa Kepri, 2024)
This research focuses on empowering coffee farmers in Enrekang Regency through transforming coffee husk waste into alternative fermented feed, using a counseling approach. Coffee husk waste is a common environmental problem in coffee producing areas, but has great potential to be processed into value-added products. A counseling approach is used to assist farmers in understanding the fermentation process, overcoming challenges, and improving their technical skills. The methods applied include direct training, ongoing assistance, and evaluation of the application of fermentation technology. The research results show that the counseling approach significantly increases farmers' knowledge and skills in processing coffee husk waste into fermented feed. The fermented feed produced is proven to have good nutritional quality and can be used as an economical and environmentally friendly alternative feed for livestock. Farmers involved in this program report increased income and reduced environmental problems caused by coffee husk waste. In conclusion, the counseling approach in empowering coffee farmers is not only effective in overcoming the problem of agricultural waste, but also contributes to improving farmer welfare through technological innovation. This research recommends expanding similar programs to other coffee producing regions to improve agricultural sustainability and farmer welfare in general.